2018
DOI: 10.1155/2018/9846274
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Transcriptome Profile of Human Cumulus Cells Related to Embryo Quality via RNA Sequencing

Abstract: Selecting excellent oocytes is required to improve the outcomes of in vitro fertilization (IVF). Cumulus cells (CCs) are an integral part of the oocyte maturation process. Therefore, we sought to identify differentially expressed genes in CCs to assess oocyte quality and embryo development potential. We divided the participants' embryos into the high-quality embryo group and low-quality embryo group by the information including age, body mass index, and the levels of luteinizing hormone, follicle-stimulating h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The eCG uses also upregulated the methyltransferases ( Oocyte imprints seems to be established in later oocyte development stages (Lucifero, Mertineit, Clarke, Bestor, & Trasler, 2002;Obata & Kono, 2002;Obata et al, 1998;Tada et al, 2000) which could be linked with the higher expression previous found of these three DNMTs in mouse (Uysal, Ozturk, & Akkoyunlu, 2017) Furthermore, we found that NDUFA1, a mitochondrial antioxidant enzyme that is expressed in response to oxidative and endoplasmic reticulum stresses, that was upregulated in human cumulus cells from oocytes yielding low-quality embryos and from oocytes failing in fertilization (Liu et al, 2018), and was 300-fold downregulated in the FSH/eCG group.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The eCG uses also upregulated the methyltransferases ( Oocyte imprints seems to be established in later oocyte development stages (Lucifero, Mertineit, Clarke, Bestor, & Trasler, 2002;Obata & Kono, 2002;Obata et al, 1998;Tada et al, 2000) which could be linked with the higher expression previous found of these three DNMTs in mouse (Uysal, Ozturk, & Akkoyunlu, 2017) Furthermore, we found that NDUFA1, a mitochondrial antioxidant enzyme that is expressed in response to oxidative and endoplasmic reticulum stresses, that was upregulated in human cumulus cells from oocytes yielding low-quality embryos and from oocytes failing in fertilization (Liu et al, 2018), and was 300-fold downregulated in the FSH/eCG group.…”
Section: Discussionmentioning
confidence: 52%
“…CPT1B , an enzyme required for the net transport of long‐chain fatty acyl‐CoAs from the cytoplasm into the mitochondria to for β‐oxidation fate, and VCAN , an extracellular matrix proteoglycan and a key biomarker of pregnancy outcome (Gebhardt, Feil, Dunning, Lane, & Russell, ; Kusano, Tsujihara, Masui, Kozai, & Takeuchi, ; Russell, Doyle, Ochsner, Sandy, & Richards, ; Wathlet et al, ; Xu, Chen, Zhang, Wei, & Cao, ),were upregulated in the FSH/eCG group. Furthermore, we found that NDUFA1 , a mitochondrial antioxidant enzyme that is expressed in response to oxidative and endoplasmic reticulum stresses, that was upregulated in human cumulus cells from oocytes yielding low‐quality embryos and from oocytes failing in fertilization (Liu et al, ), and was 300‐fold downregulated in the FSH/eCG group.…”
Section: Discussionmentioning
confidence: 96%
“…thought to modulate cell proliferation and apoptosis, although its mechanism of action is unclear. 55 In addition, transcriptome profiling of human CGCs revealed that VCAN was positively associated with embryo quality, 74 which may contribute to the retarded development we observe in IR-CKO blastocysts. Another putative TCF3-regulated factor of relevance is Secretogranin II (SCG2), which is induced in granulosa cells during the periovulatory window.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study, among many others, showed the connection between the CCs transcriptomic profile and embryo quality. Authors reported that the differential gene expression profile of human CCs, including MSTN, CTGF, NDUFA1, VCAN, SCD5 and STAR, can be used as potential indicators of embryo quality [ 24 ]. Thus, the parameters analyzed provide an indication of the competence and quality of the oocyte through positive and negative association with the gene expression profile and, furthermore, may act as positive/negative predictors of the embryo quality itself and pregnancy outcome.…”
Section: Methodsmentioning
confidence: 99%